2008
DOI: 10.2527/jas.2007-0565
|View full text |Cite
|
Sign up to set email alerts
|

Effects of conventional and grass-feeding systems on the nutrient composition of beef1

Abstract: The objectives of this study were to determine the nutrient composition of grass-fed beef in the United States for inclusion in the USDA National Nutrient Database for Standard Reference, and to compare the fatty acid composition of grass-fed and conventionally fed (control) beef. Ground beef (GB) and strip steaks (SS) were collected on 3 separate occasions from 15 grass-fed beef producers that represented 13 different states, whereas control beef samples were collected from 3 regions (Ohio, South Dakota, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

30
126
6
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(169 citation statements)
references
References 33 publications
30
126
6
7
Order By: Relevance
“…The intramuscular fat from animals fed on pasture had a higher percentage of C18:1 t-11 (vaccenic acid) than that from the other finishing treatments (P≤0.05), which was consistent with other studies (Leheska et al, 2008;García et al, 2008). The C18:1 t-11 is an intermediate in the biohydrogenation of linoleic (C18:2 n-6) and linolenic (C18:3 n-3) acids and was higher in beef from pasture-fed cattle.…”
Section: Intramuscular Fatty Acid Compositionsupporting
confidence: 82%
See 1 more Smart Citation
“…The intramuscular fat from animals fed on pasture had a higher percentage of C18:1 t-11 (vaccenic acid) than that from the other finishing treatments (P≤0.05), which was consistent with other studies (Leheska et al, 2008;García et al, 2008). The C18:1 t-11 is an intermediate in the biohydrogenation of linoleic (C18:2 n-6) and linolenic (C18:3 n-3) acids and was higher in beef from pasture-fed cattle.…”
Section: Intramuscular Fatty Acid Compositionsupporting
confidence: 82%
“…The concentration of conjugated linoleic acid c-9 t-11 in adipose tissue is higher when animals are fed on pasture than when fed on stored forage or grain (Schor et al, 2008). Other studies also showed that steers finished on pasture had higher beef contents of CLA c-9 t-11 than those finished on grain-based diets (Realini et al, 2004;Garcia et al, 2008;Leheska et al, 2008;.…”
Section: Intramuscular Fatty Acid Compositionmentioning
confidence: 63%
“…It is also important to note that, on average, t10-18:1 and t11-18:1 would constitute about 52% and 15% of total t18:1, respectively, in both regular ground beef and lean steak. Current results also indicate that feeding a high barley-grain diet like most concentrate-based diets (Dugan et al, 2007;Kraft et al, 2008;Leheska et al, 2008) increased levels of trans fatty acids other than t11-18:1 in beef compared with high-forage diets. In this context, it could, therefore, be important to re-examine the exclusion of t18:1 isomers from compulsory labelling of trans fatty acids in ruminant-derived foods.…”
Section: Discussionsupporting
confidence: 48%
“…In this sense, other studies have also found that steers fed on grass had higher C18:1 t-11 than those fed on grainbased diets (Leheska et al, 2008;Garcia et al, 2008). Moreover, some studies suggest a linear increase in CLA c-9, t-11 synthesis as the C18:1 t-11 content of the diet increased in human subjects (Salminen et al, 1998;Turpeinen et al, 2002a), whereas, the rate of conversion of C18:1 t-11 to CLA c-9, t-11 was estimated to range from 5 to 12% in rodents to 19 to 30% in humans (Turpeinen et al, 2002b).…”
Section: Longissimus Thoracis Intramuscular Fatty Acid Compositionmentioning
confidence: 83%